T25 repeat in the 3′ untranslated region of the CASP2 gene: a sensitive and specific marker for microsatellite instability in colorectal cancer - Findeisen, Peter; Kloor, Matthias; Merx, Sabine; Sutter, Christian; Wörner, Stefan M.; Dostmann, Nicole; Benner, Axel; Dondog, Bolormaa; Pawlita, Michael; Dippold, Wolfgang; Wagner, Rudolf; Gebert, Johannes; et al. (Cancer research, 2005)
DNA mismatch repair deficiency is observed in about 10% to 15% of all colorectal carcinomas and in up to 90% of hereditary nonpolyposis colorectal cancer (HNPCC) patients. Tumors with mismatch repair defects acquire mutations in short repetitive DNA sequences, a phenomenon termed high-level microsatellite instability (MSI-H). The diagnosis of MSI-H in colon cancer is of increasing relevance, because MSI-H is an independent prognostic factor in colorectal cancer, seems to influence the efficacy of adjuvant chemotherapy, and is the most important molecular screening tool to identify HNPCC patients. To make MSI typing feasible for the routine pathology laboratory, highly reproducible and cost effective laboratory tests are required. Here, we describe a novel T25 mononucleotide marker in the 3′untranslated region of the CASP2 gene (CAT25) that displayed a quasimonomorphic repeat pattern in normal tissue of 200 unrelated individuals of Caucasian origin. In addition, CAT25 was monomorphic also in all tested donors of African and Asian origin (n = 102 and n = 79, respectively) and thus differs from the most commonly used markers BAT25 and BAT26. Without the analysis of corresponding normal tissue, CAT25 correctly detected 56 of 57 colorectal cancer specimens classified as MSI-H by using the standard National Cancer Institute/International Collaborative Group-HNPCC marker panel. Combined with the standard markers BAT25 and BAT26 in a multiplex PCR, all MSI-H colorectal cancer samples were typed correctly. No false-positive results were obtained in 60 non-MSI-H control colorectal cancer specimens. These data suggest that CAT25 should be included into novel marker panels for microsatellite testing thus allowing for a significant reduction of the complexity and costs of MSI typing. Moreover, CAT25 represents a highly promising marker for early detection of colorectal cancer in HNPCC germ line mutation carriers.